1989
DOI: 10.1007/bf00250573
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning in monkeys (Macaca fascicularis) with lesions in motor thalamus

Abstract: The study examines the nature of the influence that the basal ganglia exert on frontal cortex via the motor nuclei of the thalamus. Twelve monkeys were trained to pull a handle given one colour cue and to turn it given another. Bilateral lesions were then placed in the ventral thalamus. Four monkeys with large anterior lesions including the VA nucleus and the anterior part of VLo were severely impaired at relearning the task. Monkeys with small lesions in VAmc or with lesions centred on VLo were not impaired. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 29 publications
2
63
0
Order By: Relevance
“…Studies of lesioning in the primate have found that pharmacologic (transient) inactivation of the basal ganglia receiving territory of the ventral motor thalamus resulted in a reduced number of internally or externally triggered movements and an increased reaction time (depending on the injection site), with no obvious effect on spontaneous movements outside the task [53]. Large bilateral permanent lesions interrupting the basal ganglia receiving areas and sparing the cerebellar receiving areas resulted in impaired motor learning without a significant effect on spontaneous movements, providing evidence for a role of the basal ganglia-thalamocortical components of the motor circuit in motor learning [54]. In contrast, interventions at the PPN level in primates seem to have more overt effects on spontaneous behavior, resulting in akinesia/bradykinesia [55].…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 93%
“…Studies of lesioning in the primate have found that pharmacologic (transient) inactivation of the basal ganglia receiving territory of the ventral motor thalamus resulted in a reduced number of internally or externally triggered movements and an increased reaction time (depending on the injection site), with no obvious effect on spontaneous movements outside the task [53]. Large bilateral permanent lesions interrupting the basal ganglia receiving areas and sparing the cerebellar receiving areas resulted in impaired motor learning without a significant effect on spontaneous movements, providing evidence for a role of the basal ganglia-thalamocortical components of the motor circuit in motor learning [54]. In contrast, interventions at the PPN level in primates seem to have more overt effects on spontaneous behavior, resulting in akinesia/bradykinesia [55].…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 93%
“…However, this view fails to explain several clinical and experimental observations, such as the fact that lesions of the motor thalamus do not result in akinesia [15] or that globus pallidus lesions do not improve it [16]. Consequently, the dysfunction of the motor circuit cannot alone account for akinesia.…”
Section: From the Motor To The Executive Hypothesismentioning
confidence: 97%
“…Regarding the motor thalamus, the PMdc receives inputs from the oral and caudal parts of ventral lateral nucleus (VLo and VLc), whereas the main source of thalamic input to the PMv is area X and the ventral posterior lateral nucleus (Kurata 1994(Kurata , 2005Matelli et al 1989;Schell and Strick 1984). However, it has been demonstrated that monkeys with large anterior thalamic lesions, including in the ventral anterior nucleus and the anterior part of the VLo, were severely impaired at relearning a conditional motor task (Canavan et al 1989). Accordingly, inputs from the rostral motor thalamic nuclei to the PMdc may play a prominent role in conditional motor behavior.…”
Section: Specificity Of the Pmdc In Controlling Conditional Motor Behmentioning
confidence: 99%